The Relationship of Mental and Behavioral Disorders to All-Cause Mortality in a 27-Year Follow-up of 4 Epidemiologic Catchment Area Samples - Eaton, W. W.; Roth, K. B.; Bruce, M.; Cottler, L.; Wu, L.; Nestadt, G.; Ford, D.; Bienvenu, O. J.; Crum, R. M.; Rebok, G.; Anthony, J. C.; Munoz, A. (American journal of epidemiology, 2013)
Subjects from the Epidemiologic Catchment Area Program, interviewed during 1979-1983, were linked to data in the National Death Index through 2007 to estimate the association of mental and behavioral disorders with death. There were more than 25 years of follow-up for 15,440 individuals, with 6,924 deaths amounting to 307,881 person-years of observation. Data were analyzed by using age as the time scale and parametric approaches to quantify the years of life lost due to disorders. Alcohol, drug use, and antisocial personality disorders were associated with increased risk of death, but there was no strong association with mood and anxiety disorders. Results of high- and low-quality matches with the National Death Index were similar. The 3 behavioral disorders were associated with 5-15 years of life lost, estimated along the life course via the generalized gamma model. Regression tree analyses showed that risk of death was associated with alcohol use disorders in nonblacks and with drug disorders in blacks. Phobia interacted with alcohol use disorders in nonblack women, and obsessive-compulsive disorder interacted with drug use disorders in black men. Both of these anxiety disorders were associated with lower risk of death early in life and higher risk of death later in life.